Tissue Doppler-derived index of left ventricular filling pressure, E/E′, predicts survival of patients with non-valvular atrial fibrillation. Issue 9 (31st January 2006) - Okura, H; Takada, Y; Kubo, T; Iwata, K; Mizoguchi, S; Taguchi, H; Toda, I; Yoshikawa, J; Yoshida, K
Abstract : Objectives: To investigate whether the ratio of early transmitral flow velocity (E) to early diastolic mitral annular velocity (E′) predict prognosis in patients with non-valvular atrial fibrillation. Methods: 230 patients with non-valvular atrial fibrillation were enrolled and studied. According to E/E′ value, patients were divided into groups with lower (group A with E/E′ ⩽ 15) and higher (group B with E/E′ > 15) E/E′. Results: During follow up (average 245 days), 21 (9.1%) deaths were documented. All cause death (15/90 (16.7%) v 6/140 (4.3%)), cardiac death (10 (11.1%) v 2 (1.4%)) and congestive heart failure (16 (17.8%) v 8 (5.7%)) were more common in group B than in group A (all p < 0.01). A Kaplan–Meier survival curve showed that the cumulative survival rate was significantly lower in group B than in group A (log rank p  =  0.0013). By multivariate logistic regression analysis, E/E′ (χ 2  =  4.47, odds ratio (OR) 1.05, 95% confidence interval (CI) 1.01 to 1.11, p  =  0.03) and age (χ 2  =  6.45, OR 1.06, 95% CI 1.01 to 1.11, p  =  0.02) were independent predictors of mortality. Conclusion: The Doppler-derived index of left ventricular filling pressure, E/E′, is a powerful predictor of the clinical outcome of patients with non-valvular atrial fibrillation.